The kaleidoscope model of food security reform: Introduction and applications to input subsidy policies - Resnick, Danielle (2017)
Danielle Resnick POLICY SEMINAR What Drives Policy Change? Insights from the Kaleidoscope Model of Food Security Policy Organized by IFPRI, Michigan State University and University of Pretoria, Consortium partners- Food Security Policy Innovation Lab